2020
DOI: 10.1007/s00779-020-01405-3
|View full text |Cite
|
Sign up to set email alerts
|

Materialising contexts: virtual soundscapes for real-world exploration

Abstract: This article presents the results of a study based on a group of participants' interactions with an experimental sound installation at the National Science and Media Museum in Bradford, UK. The installation used audio augmented reality to attach virtual sound sources to a vintage radio receiver from the museum's collection, with a view to understanding the potentials of this technology for promoting exploration and engagement within museums and galleries. We employ a practice-based design ethnography, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In such contexts, sound has the potential to create a more individualized experience for spectators by adapting to their "goals, preferences, knowledge, and interests," as Andreas Zimmermann and Andreas Lorenz have persuasively shown [5]. It also may provide a catalyst both for acquiring knowledge and for evoking "personal memories associated with a museum artifact," as Laurence Cliffe et al recently revealed [6]. That all said, relatively little existing scholarship has addressed the ways in which sound design shapes the experiences of audiences within VEs.…”
Section: Introductionmentioning
confidence: 99%
“…In such contexts, sound has the potential to create a more individualized experience for spectators by adapting to their "goals, preferences, knowledge, and interests," as Andreas Zimmermann and Andreas Lorenz have persuasively shown [5]. It also may provide a catalyst both for acquiring knowledge and for evoking "personal memories associated with a museum artifact," as Laurence Cliffe et al recently revealed [6]. That all said, relatively little existing scholarship has addressed the ways in which sound design shapes the experiences of audiences within VEs.…”
Section: Introductionmentioning
confidence: 99%
“…Sound has long been known to have the potential to give museum exhibits additional emotional power [1] as well as allowing visitors to generate different interpretative perspectives on an exhibit [2], [3]. Consequently, museums have begun to explore sound in order to produce more entertaining exhibitions [4]. The LISTEN system [5] is an audio augmented reality (AAR) system for museum exhibits which tracks visitor behaviour in order to adjust delivery of the audio content of the exhibition.…”
Section: Introductionmentioning
confidence: 99%